2014
DOI: 10.1371/journal.pone.0098605
|View full text |Cite
|
Sign up to set email alerts
|

The Functional and Palaeoecological Implications of Tooth Morphology and Wear for the Megaherbivorous Dinosaurs from the Dinosaur Park Formation (Upper Campanian) of Alberta, Canada

Abstract: Megaherbivorous dinosaurs were exceptionally diverse on the Late Cretaceous island continent of Laramidia, and a growing body of evidence suggests that this diversity was facilitated by dietary niche partitioning. We test this hypothesis using the fossil megaherbivore assemblage from the Dinosaur Park Formation (upper Campanian) of Alberta as a model. Comparative tooth morphology and wear, including the first use of quantitative dental microwear analysis in the context of Cretaceous palaeosynecology, are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 118 publications
(172 reference statements)
4
122
0
Order By: Relevance
“…This is approximately equivalent to that predicted for a large elephant subsisting on dry vegetation (Laws 1970). Of course, these nutritional requirements could have been attained more efficiently through the added consumption of energy-rich fruiting bodies, for which the miniscule, cusp-like teeth (Mallon and Anderson 2014b), and comparably selective beak shape of Ankylosaurus (particularly in relation to Euoplocephalus; Ősi et al 2017) were apparently well adapted. Small and nutritious invertebrates may also have supplemented the diet on occasion (see below).…”
Section: Arbour and Mallonmentioning
confidence: 68%
See 2 more Smart Citations
“…This is approximately equivalent to that predicted for a large elephant subsisting on dry vegetation (Laws 1970). Of course, these nutritional requirements could have been attained more efficiently through the added consumption of energy-rich fruiting bodies, for which the miniscule, cusp-like teeth (Mallon and Anderson 2014b), and comparably selective beak shape of Ankylosaurus (particularly in relation to Euoplocephalus; Ősi et al 2017) were apparently well adapted. Small and nutritious invertebrates may also have supplemented the diet on occasion (see below).…”
Section: Arbour and Mallonmentioning
confidence: 68%
“…Lyson and Longrich (2011) found it made up <0.05% of associated dinosaur specimens from the Hell Creek, Lance, and equivalent formations, Wilson (2008) found it was less than 0.05% of isolated specimens from microvertebrate localities, and Horner et al (2011) did not recover any specimens from the middle or upper third of the Hell Creek Formation and found it was 5% of the fauna in the lower third. Ankylosaurus may have been ecologically rare, or it may have been an infrequent visitor to the coastal plain depositional environments where it was more likely to fossilize (similar comments were made by Mallon and Anderson (2014b) concerning ankylosaurids from the older Dinosaur Park Formation). Carpenter (2004) suggested that the late Maastrichtian Edmontonia sp.…”
Section: Size Of Ankylosaurusmentioning
confidence: 77%
See 1 more Smart Citation
“…For instance, the diverse rounded-to-spade-shaped, denticulate, and often precisely occluding dentition of ornithischian dinosaurs has greatly informed paleontologists and functional anatomists of their past feeding behavior. In accordance with their morphological diversity, macro-and microscopic dental wear patterns have provided direct evidence of true feeding motions of the lower jaw during feeding, including orthal (i.e., dorsoventral, or up-and-down, jaw motion), palinal motion (i.e., caudally oriented, or backward, jaw motion while teeth are occluded), and long-axis rotation of each side of the jaw at the predentary joint (Mallon and Anderson 2014;Nabavizadeh and Weishampel 2016). These feeding motions vary both between and among clades of Ornithischia, and each gives a paleoecological context of the animals' respective time periods (Nabavizadeh 2016).…”
Section: Functional Morphologymentioning
confidence: 93%
“…Some studies described striated surfaces on dinosaur teeth and suggested they are directly related to mastication (Weishampel 1984;Fiorillo 1991Fiorillo , 1995Fiorillo , 1997Fiorillo , 1998Weishampel & Norman 1989;Upchurch & Barrett 2000;Barrett 2001;Rybczynski & Vickaryous 2001;Sankey et al 2002;D'Amore 2009;Erickson et al 2012bErickson et al , 2015Sereno 2012;Mallon & Anderson 2014). Most of these studies analysed herbivorous ornithischians and sauropods, by comparing and contrasting the feeding habits of theropods, varanids, crocodyliforms and mammals.…”
mentioning
confidence: 99%